Studies on the Medicinal Plant Acalypha Wilkesiana Ethanol Extract Phytocomponents by GCMS Analysis (Global Journal of Science Frontier Research, 2016)
The ethanolic extract of the leaves of Acalypha wilkesiana plant was studied to find the phytochemical compounds using GCMS analysis. The result of the phytochemical analysis revealed the presence of 12 compounds. Among the 12 compounds, the most abundant were 2-Ethyl-1-hexene with 39.21 peak area %, RT 22.698 and molecular formula C 8 H 16 ; n-Haxadecanoic acid or plamitic acid with 20.92 peak area %, RT:20.92 and molecular formula C 16 H 32 O 2 and Butane 1,4-diol with 11.58%peak area RT:8.358 and molecular formula of C 4 H 10 O 2 .which demonstrated various medicinal potentials. Therefore the ethanolic leaf extract of Acalypha wilkesiana contain pharmacologically useful active phytochemicals which have effect on progesterone receptors, glucocorticoid receptors, androgen and estrogen receptors with a mild antioxidant and atherosclerotic activity thus could play vital roles in health care programs.
Keywords: acalypha wilkesiana; acetophenone; GCMS; n-Hexadecanoic acid; progesterone receptor